Design and Elevating Cloud Security Through a Comprehensive Integration of Zero Trust Framework - Saravanan, K.; Anitha, R.; Kamarajapandian, P.; Arockiadoss, Thomas Paul Roy; Kumar, K. Sambath; Hariharan, R. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Cloud security is vital as it protects against a myriad of cyber threats, including data breaches and service disruptions, ensuring the integrity, confidentiality, and availability of critical information stored in the cloud. It also establishes a foundation for trust, enabling businesses to harness the benefits of cloud technologies while maintaining the resilience and security of their digital assets. User authentication within the cloud ecosystem is indispensable, constituting a foundational pillar for the security and integrity of digital assets. By validating user identities, organizations establish a crucial defense mechanism, thwarting unauthorized access to sensitive data and resources. This authentication process is pivotal in enforcing stringent access controls, effectively mitigating the risks associated with data breaches and unauthorized transactions. The Zero Trust Framework is a security paradigm commencing with User Identity Verification and advancing through the seamless integration of Multi-Factor Authentication (MFA), Device Health Assessment, and Behavioral Analysis. The dual-layer authentication process establishes a formidable barrier, ensuring access only for legitimate users, while stringent device health checks enforce security criteria compliance. The orchestration of Behavioral Analysis, powered by machine learning, becomes pivotal in continuous monitoring, promptly identifying deviations from typical user behavior. These anomalies act as proactive indicators, triggering investigations into potential security breaches. This integrated security approach, providing a robust foundation for continuous verification in safeguarding against unauthorized access and potential threats.